Hamka's transcendental values in Pribadi Hebat: Bridging philosophical thought and contemporary character education - Ari Mulyono; Amirul Bakhri (Mishkat: Journal of Theology and Civilization, 2026)
Character education requires a strong spiritual foundation to develop individuals with integrity. However, studies on transcendental values in Hamka's Pribadi Hebat have largely been limited to identifying educational values without proposing a conceptual implementation model for contemporary character education. This study aims to analyze the transcendental values presented in Pribadi Hebat and develop their implementation model for character education. A qualitative library research approach was employed, and the data were analyzed using qualitative content analysis of Hamka's major works and relevant supporting literature. The findings reveal that transcendental values consist of three interconnected dimensions—aqidah, ibadah, and akhlak—which collectively form an integrated framework for personality development. Based on these findings, this study proposes a conceptual model linking transcendental values with the curriculum, teachers, family, school culture, community, and the digital environment to foster a great personality. The proposed model extends Hamka's philosophical thought into a more applicable framework for contemporary character education. Abstrak Pendidikan karakter memerlukan fondasi spiritual yang kuat agar mampu membentuk pribadi yang berintegritas. Namun, kajian mengenai nilai transendensi dalam Pribadi Hebat karya Hamka masih didominasi oleh identifikasi nilai dan belum menghasilkan model implementasi konseptual bagi pendidikan karakter kontemporer. Penelitian ini bertujuan menganalisis nilai-nilai transendensi dalam Pribadi Hebat serta mengembangkan model implementasinya dalam pendidikan karakter. Penelitian menggunakan pendekatan kualitatif dengan jenis library research yang dianalisis melalui qualitative content analysis terhadap karya-karya Hamka dan literatur pendukung yang relevan. Hasil penelitian menunjukkan bahwa nilai transendensi terdiri atas tiga dimensi utama, yaitu aqidah, ibadah, dan akhlak, yang membentuk sistem pembinaan kepribadian secara terpadu. Berdasarkan temuan tersebut, penelitian ini menghasilkan model konseptual yang menghubungkan nilai transendensi dengan kurikulum, guru, keluarga, budaya sekolah, masyarakat, dan lingkungan digital menuju pembentukan great personality. Model ini memperluas pemikiran Hamka dari ranah filosofis menuju kerangka implementasi pendidikan karakter yang lebih aplikatif.